آپﷺ کی تاریخِ پیدائش کے بارے میں منقول روایات کاایک تحقیقی جائزہ - Haroon Ur Rashid Khan; Aziz Ahmad Chatrali (الضحی, 2021)
Allah Almighty Created human beings with a lot of qualities. Sometimes when these qualities appear in someone he Perform such action which make history. How much qualities has bestowed upon Prophet Muhammad (SAW) by Allah is beyond of human intellect. Biographers mentioned every aspect of life in the book of Prophet Muhammad (SAW) seerah (Biography). Even his personal life is presented in books of seerah. With this there are differences among religious scholar that on what day of Rabi ul awal Prophet Muhammad (SAW) was born in the wp coming article we will discuss different views about the date of birth of Prophet Muhammad (SAW). Then in the of religious scholar we will Sealed the pre pondering view